2018
DOI: 10.1063/1.5047547
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh detection sensitivity exceeding 105 V/W in spin-torque diode

Abstract: Microwave detection has a huge number of applications in physics and engineering. It has already been shown that biased spin torque diodes have performance overcoming the CMOS counterpart in terms of sensitivity. In this regard, the spin torque diodes are promising candidates for the next generation of microwave detectors. Here, we show that the optimization of the rectification process based on the injection locking mechanism gives an ultrahigh sensitivity exceeding 200 kV/W with an output resistance below 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 24 publications
1
36
0
Order By: Relevance
“…After a proper rectification process optimization, the STD based on injection‐locking mechanism demonstrated the highest sensitivity [ 36 ] up to date, which exceeding 210 000 mV mW −1 . It has become possible through a systematic study of the detection properties by adjusting the CoFeB free layer thickness for optimizing the interfacial perpendicular magnetic anisotropy (IPMA), and by balancing it with the shape anisotropy (cross‐section geometry) of the STDs.…”
Section: Spin‐torque Diode Effect In Case Of DC Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…After a proper rectification process optimization, the STD based on injection‐locking mechanism demonstrated the highest sensitivity [ 36 ] up to date, which exceeding 210 000 mV mW −1 . It has become possible through a systematic study of the detection properties by adjusting the CoFeB free layer thickness for optimizing the interfacial perpendicular magnetic anisotropy (IPMA), and by balancing it with the shape anisotropy (cross‐section geometry) of the STDs.…”
Section: Spin‐torque Diode Effect In Case Of DC Biasmentioning
confidence: 99%
“…The required magnetization state, which is almost perpendicular but has some small tilt from normal, can also be achieved using perpendicular magnetic anisotropy. For example, in the work by Zhang et al., [ 36 ] the authors succeed to observe broadband detection (from 0.2 to 0.6 GHz) in MTJ with free layer magnetization 11° tilted from normal in the presence of DC bias but without perpendicular external field. This regime in some way is similar to the vortex expulsion case mentioned above, since it also requires DC bias to set the system into the maximum amplitude precession state and it switches into the resonant regime without it.…”
Section: Broadband Std Rectification Modementioning
confidence: 99%
“…Platinum. We perform systematic micromagnetic simulations to calculate the skyrmion sizes as a function of the out-of-plane external field 0Hext and temperature T, by integrating the Landau-Lifshitz-Gilbert equation for the reduced magnetization T=0 K, we used the following material parameters: s M =600 kA/m [12], A =20 pJ/m [49], D =3.0 mJ/m 2 [50,51], u K =0.60 MJ/m 3 [12,52], and Gilbert damping G  =0.1 [53], while for T>0 and the analytical model, we used the parameters as calculated from the scaling relations [35]     It can be observed that there exist skyrmion configurations with different shape and size (Figs. 1(b)-(e)), but characterized by the same energy (5.6 x 10 -17 J in Fig.…”
Section: Numerical Modelmentioning
confidence: 99%
“…It should be mentioned that there have been a lot of important proposals about switching, creation, and excitation of a magnetic vortex or magnetic skyrmion confined in a nanodot using the microwave irradiation so far [53][54][55][56][57] . These methods cleverly avoid the difficulty in squeezing a spot of microwave application by restricting the magnetization distribution to a nanometric dot-shaped sample.…”
Section: Summary and Discussionmentioning
confidence: 99%